Group Compassion-Based Therapy for Female Survivors of Intimate-Partner Violence and Gender-Based Violence: a Pilot Study - Naismith, Iona (Journal of family violence, 2021)
Emotional disorders are common in survivors of gender-based violence, especially intimate partner violence (IPV), and are often maintained by shame and self-criticism. Compassion-based therapies target shame and self-criticism but have not been evaluated in this population to date, nor in any low- or middle-income country. Ten Colombian females reporting recent gender-based violence and clinical levels of emotional disorder(s) completed a 5-session group compassion-based therapy intervention. Measures of symptoms and hypothesized mediators were applied 5 weeks before treatment (baseline), pre-treatment, post-treatment and 3-month follow-up. At follow-up, 56 to 89% of cases showed reliable symptom change (depending on the measure). Self-inadequacy, guilt cognitions and experiential avoidance may be important mediators of change. Findings indicate that compassion-based interventions may benefit this population, even for women remaining in relationships with IPV, those with low formal education, and in contexts where gender-based violence is a social norm.